Genetic rescue to the rescue. (January 2015) - Whiteley, Andrew R.; Fitzpatrick, Sarah W.; Funk, W. Chris; Tallmon, David A.
Highlights Genetic rescue is difficult to detect at the population level. Recent studies show genetic rescue is a more powerful tool than has been appreciated. Genomics provide a useful way to advance genetic rescue research and application.